Morphological characters, phenolic and flavonoid contents of Vitex trifolia accessions from Lamongan District, Indonesia - AFIFATUN NISA; ANI KURNIAWATI; DIDAH NUR FARIDAH (Society for Indonesian Biodiversity, 2023)
Abstract. Nisa A, Kurniawati A, Faridah DN. 2023. Morphological characters, phenolic and flavonoid contents of Vitex trifolia accessions from LamonganDistrict, Indonesia. Biodiversitas 24: 1635-1641. Indonesia is a country with high biodiversity. Legundi (Vitex trifolia L.) is one of the plant species that has long been used as a raw material for traditional herbal medicine. This study aims to determine the morphological, agronomic, leaf production, and total phenolic and total flavonoid content of the V. trifolia accession from Lamongan District, East Java, Indonesia. Morphological and agronomic characterizations were observed using qualitative and quantitative parameters. The colorimetric method determined the total phenolic and flavonoid content in V. trifolia extract. The results showed differences in morphological and agronomic characters between accessions. The Bluluk accession had the highest leaf production that did not differ from the Pucuk, Sekaran, and Kedumpring accessions, while the Modo accession had the lowest. There was no difference in total phenol and flavonoid content between accessions. Leaves had the highest total phenolic content (3210.57 GAE mg/100 g dry powder), followed by twigs (1331.98 GAE mg/100 g dry powder) and fruit (973.77 GAE mg/100 g dry powder). Leave also contained the highest flavonoid content (1792.90 QE mg/100 g dry powder).The highest phenolic and flavonoid content in the leaves of V. trifoliamay support its use in traditional medicine.